The stars the definitive visual guide to the cosmos - Dinwiddie, Robert 1953-; Hughes, David W. (David Wolstenholme) 1941-; Jones, Geraint H.; Ridpath, Ian; Stott, Carole; Sparrow, Giles 1970- (Dorling Kindersley Limited, 2016)
The definitive visual guide to exploring all the marvels of the stars, the Milky Way, and the universe beyond. Chart the wonders of the cosmos in our own solar system and beyond with The Stars. Packed with 3-D artworks of each constellation and incredible new imagery from the Hubble Space Telescope, ground-based observatories worldwide, and more, this awe-inspiring guide features the most fascinating objects known to astronomy, from glittering star-birth nebulae to supermassive black holes. The position, size, and color of every night-sky object is revealed with unprecedented clarity, and a specially commissioned 3-D model of the celestial sphere that surrounds our planet charts all 88 constellations, together forming a complete map of the sky. From the Big Bang to the search for extraterrestrial life, key areas in astronomy and cosmology are covered, and colorful infographics distill a wealth of data into an easy-to-digest visual format. Whether you want to know more about space and the night sky or are eager to take up stargazing, The Stars is your guide to exploring these fascinating marvels of the universe.